2023
DOI: 10.1111/mec.16959
|View full text |Cite
|
Sign up to set email alerts
|

Indirect maternal effects via nest microbiome composition drive gut colonization in altricial chicks

Abstract: Complex and heterogeneous gut microbial communities affect vertebrate host physiology, development and behaviour, with ramifications for host ecology and evolution (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 144 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…A plethora of studies have reported robust links between the nesting environment and chick gut microbiota [ 26 , 28 , 36 , 98 ]. Our findings align with the ”nidobiome” concept, which integrates the collective effects of parents, nest conditions, and nestling interactions during microbiome assembly and their contribution over the developmental stages [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of studies have reported robust links between the nesting environment and chick gut microbiota [ 26 , 28 , 36 , 98 ]. Our findings align with the ”nidobiome” concept, which integrates the collective effects of parents, nest conditions, and nestling interactions during microbiome assembly and their contribution over the developmental stages [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to sex, this could be attributed to the relatively short time frame of this study, which may not have allowed hierarchical differences among chicks to become evident. The nesting environment appears to have a homogenising effect on microbiota diversity across the brood, surpassing other potential factors like dominance rank in its influence [ 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of each unique genera belonging to the required group was divided by the total number of samples in that group to estimate the sample coverage in %. The core microbiota members were selected from the genera in >50% of the samples ( Borroni et al, 2022 ; Diez-Méndez et al, 2023 ). The changes in the relative abundance% of the core microbes along with the growth of silver pompano (DPH wise) were also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from environmental and ecological factors, composition of the gut microbiota should be shaped by basic individual (intrinsic) traits, such as sex or age (Matheen et al 2022 ). So far, most information on this intrinsic variation originates from poultry research (van Dongen et al 2013 ), but field studies on wild birds supported substantial role of vertical microbe transfer during feeding between hatchings and their parents as the main factor responsible for establishment of gut symbionts (Diez-Méndez et al 2023 ). At the same time, little is known about how bacterial communities within the gastrointestinal tract change with age in wild birds after fledging period, but scant evidence suggest that first year/immature birds host less diverse bacterial communities than adult/mature individuals (Kohl et al 2019 , Hernandez et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%